2017
DOI: 10.1177/1054773817719379
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glucose Values of Blood Samples Taken in Three Different Ways

Abstract: The purpose of the study was to determine differences and correlations between the blood glucose values of venous blood and the first and second drops of capillary blood samples taken in three different ways. Blood samples were (a) venous blood, (b) the first and second drops of capillary blood from the middle finger of the right hand (only washed with soap and water), and (c) the first and second drops of capillary blood from the middle finger of the left hand (washed with soap and water and cleaned with alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…Significantly lower home-measured FBGs were found in FBG sub-group of <100mg/dl, ≥126mg/dl sub-groups, and in total subjects; except for 100-125mg/dl with an insignificantly different value. The result was different from the previous studies, in which the blood sugar level obtained from the clinic was lower than the home measurement (Boyd et al, 2005;Midilli et al, 2019). A study with a higher value of capillary whole blood sugar level done using the 2-hour OGTT had an increase of 0.8 mmol/L sugar level compared to the method measured using venous laboratory plasma sugar (Blaurock et al, 2018).…”
Section: Subjects' Characteristicscontrasting
confidence: 59%
See 1 more Smart Citation
“…Significantly lower home-measured FBGs were found in FBG sub-group of <100mg/dl, ≥126mg/dl sub-groups, and in total subjects; except for 100-125mg/dl with an insignificantly different value. The result was different from the previous studies, in which the blood sugar level obtained from the clinic was lower than the home measurement (Boyd et al, 2005;Midilli et al, 2019). A study with a higher value of capillary whole blood sugar level done using the 2-hour OGTT had an increase of 0.8 mmol/L sugar level compared to the method measured using venous laboratory plasma sugar (Blaurock et al, 2018).…”
Section: Subjects' Characteristicscontrasting
confidence: 59%
“…A rural community is relatively far from health professionals and facilities. A study showed that capillary blood sugar levels could be used to replace venous blood sugar (Midilli et al, 2019). Maintenance of blood pressure, total cholesterol, and blood sugar target will reduce the atherosclerotic cardiovascular disease (ASCVD) risk, diabetes mellitus type 2, and stroke (Riddle et al, 2018;Stone et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We did not have a data about severity of illness score; however, we believe that admitting service can be used as a proxy. We were not able to confirm the source of blood for the POCG (eg, capillary, venous, and arterial), which may introduce some variability in sample measurement 33 ; however, we anticipate that the vast majority of POCG samples are indeed fingerstick capillary samples. Finally, although our nursing staffing models are based on national benchmarks and are generally consistent throughout our five hospitals, we were unable to obtain information regarding nursing-to-patient or nursing hours by patient acuity to evaluate whether nurse staffing was directly associated with our outcome.…”
Section: Discussionmentioning
confidence: 84%
“…While the American Diabetes Association (ADA, 2018) recommends testing the first blood after washing hands during blood glucose measurement, in the nursing literature, it is recommended to wash hands, wipe the finger with alcohol-infused cotton, wait for it to dry, wipe the first blood drop, and use the second drop for testing (Aştı & Karadağ, 2013;Akça Ay, 2019;Bektaş, 2015;Capple et al, 2017;Dikmen & Akın Korhan, 2016), whereas Ergin and Zaybak (2018) reported in their observational study on 60 nurses regarding the blood glucose measurement of nurses working at the clinic that nurses did not comply with asepsis principles during capillary blood glucose measurement, lancet insertion was performed without questioning washing of hands and wiping the finger with alcohol-infused cotton, and the second drop of blood was used for measurement (Ergin & Zaybak, 2018). In addition to this, there are also studies which reported that there is no difference between the glucose concentrations in the first and second drops in blood glucose measurement (Fruhstorfer & Quarder, 2009;Hortensius et al, 2010;Li et al, 2014;Palese et al, 2016;Sagkal Midilli et al, 2019). When the literature is examined, while studies on healthy individuals (Fruhstorfer & Quarder, 2009;Hortensius et al, 2010;Sagkal Midilli et al, 2019), individuals visiting for 2-hour oral glucose tolerance test (OGTT) (Li et al, 2014), and type 1 diabetes patients without hypoglycemia (Palese et al, 2016) gain attention, there is no study on whether or not there is a difference between the first and second blood drops in measurements made by fasting and at the time where the capillary value is the highest.…”
Section: Introductionmentioning
confidence: 89%
“…In addition to this, there are also studies which reported that there is no difference between the glucose concentrations in the first and second drops in blood glucose measurement (Fruhstorfer & Quarder, 2009;Hortensius et al, 2010;Li et al, 2014;Palese et al, 2016;Sagkal Midilli et al, 2019). When the literature is examined, while studies on healthy individuals (Fruhstorfer & Quarder, 2009;Hortensius et al, 2010;Sagkal Midilli et al, 2019), individuals visiting for 2-hour oral glucose tolerance test (OGTT) (Li et al, 2014), and type 1 diabetes patients without hypoglycemia (Palese et al, 2016) gain attention, there is no study on whether or not there is a difference between the first and second blood drops in measurements made by fasting and at the time where the capillary value is the highest.…”
Section: Introductionmentioning
confidence: 89%